Identification and characterization of bacteria from feces and river in East Bekasi using biochemical test - Noor Andryan Ilsan; Maulin Inggraini; Liendrie Patria Elsa; Sayyid Daffa Alfath (LPPM Universitas Negeri Jakarta, 2025)
Identification and characterization of bacteria are the two main detection in determining the species level of pathogenicity of a bacteria. This study aims to isolate bacteria from normal person faeces, liquid faeces, and some sourced from river water which is still used by local communities for bathing, swimming and fishing activities, the results of which are consumed. Water contaminated with microorganisms such as bacteria is most commonly caused by contamination from pollution, industrial waste, even animal and human faeces. The media used was selective differential Salmonella Shigella Agar (SSA) media. Colonies that grown were then characterized by testing their biochemical activity. The results of the biochemical tests were compared with Bergey's Manual of Determinative Bacteriology. From seven samples for each location, Salmonella sp. was identified from J. Kh Abu Bakar river, and E. coli was identified from Bumi Palapa river. Both of these species were categorized as human pathogens. The rest of samples were contained the opportunistic bacteria, including Enterobacter sp. and Serratia sp. This study concluded that two from seven samples location were high risk for human health.This identification can help to determine the pathogens that cause various diseases with a large impact on society.